(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the classification, biological characteristics, applications, and agricultural value of corn varieties imported from abroad to Uzbekistan. Information on the productivity, climate adaptation, and role of imported hybrid varieties as food and forage crops is also provided.